Antecedents and outcomes of job insecurity among salespeople - Bouzari, Mona; Karatepe, Osman M. (Emerald Group Publishing Ltd, 2018)
Purpose The purpose of this paper is to examine the impacts of job resources, as manifested by selective staffing, training (TR), and career opportunities, on job insecurity and the influence of job insecurity on hope, job satisfaction, and creative performance. By investigating these relationships, the present study also aims to provide the managers the ways by which they can foster job resources, reduce job insecurity, and activate hope and job outcomes of their salespeople. Design/methodology/approach Data came from hotel salespeople in Iran. Structural equation modeling was used to test the aforesaid relationships. Findings The empirical data lend support to the overwhelming majority of the relationships. Specifically, job insecurity and hope act as mediators of the impacts of job resources on job satisfaction. Job satisfaction mediates the impacts of job insecurity and hope on creative performance. Contrary to what has been hypothesized, job insecurity positively influences salespeople's hope. Such salespeople in turn exhibit higher job satisfaction. In addition, job resources do not significantly influence hope via job insecurity. Practical implications Management should invest in job resources to reduce job insecurity. Management should also try to hire individuals high on hope since hope is treated as a malleable variable and can be developed via TR interventions. Workshops can be organized to enable junior salespeople to learn senior salespeople's practices regarding the solutions to new customer requests and problems. Originality/value Job insecurity is an endemic problem in many industries and there is a lack of empirical research about the intermediate linkage between job insecurity and employees' job outcomes. There is also a need for more research to ascertain the factors influencing job insecurity.
Keywords: Job satisfaction; Job insecurity; Hope; Salespeople; Job resources; Creative performance